Entangled Standardizing Networks: The Case of GLOBALGAP and Fairtrade in St Vincent’s Banana Industry - Aasprong, Haakon (The International Journal of Sociology of Agriculture and Food, 2013)
The governance of international agribusiness has changed dramatically over the past two decades, and an important aspect of that change has been the increasing use of certification systems that cover a wide range of product and production attributes. While certification is often represented by its advocates as a depoliticized and scientific means of governing, some argue that governing by standards is better understood as an ongoing and never-ending process summed up by the term ‘standardizing work’. Expanding on this, I suggest that the twin concept of ‘standardizing network’ may be used to refer to actors and intermediaries engaged in standardizing work with reference to a particular standard. Empirically grounded in the banana industry of the eastern Caribbean island St Vincent – an industry having adopted both  GLOBALGAP and Fairtrade certification – the article examines the role of interpretation as standardizing work. Discussing the GLOBALGAP certification process, I suggest that a chain of interpretive authority is at work, which, particularly in the wake of a standard revision, encourages a stricter than necessary operationalization of requirements. Furthermore, I argue that the space opened by the absence of authoritative interpretations may invite an entanglement of standardizing networks and that an appreciation of this sometimes entangled nature of standardizing networks is necessary if we are to attain a fuller understanding of agri-food certification processes in the sphere of production. This is demonstrated empirically through an account of the influence of the Vincentian Fairtrade national farmers’ organization on the GLOBALGAP certification process.